Pengaruh Customer Centric Dan Religious Framing Terhadap Keputusan Pembelian: customer centric : religious framing : keputusan pembelian - putra, gilang kharisma; Astuti, Fitria Yuni (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to examine the effect of customer centricity and religious framing on purchasing decisions with the Hajah Subagyo restaurant as the research sample, the Hajah Subagyo restaurant was chosen because it represents the Islamic name in the business name, namely "hajah". Sampling using Accidental sampling method. This method is a technique of determining sampling based on chance, that is, anyone who meets the researcher by chance can be used as a sample. So the sample in this study were visitors to the Hajah Subagyo Kendal restaurant who accidentally visited the restaurant on the 3rd day of the data collection process. So the number of samples used in this study was obtained as many as 151 respondents who visited the Hajah Subagyo restaurant. The results of the study revealed that customer centricity and religious framing had a significant effect based on statistical tests with respective values ​​of 0.186 and 0.673.